2015
DOI: 10.1017/s0956796815000209
|View full text |Cite
|
Sign up to set email alerts
|

Interleaving data and effects

Abstract: The study of programming with and reasoning about inductive datatypes such as lists and trees has benefited from the simple categorical principle of initial algebras. In initial algebra semantics, each inductive datatype is represented by an initial f -algebra for an appropriate functor f . The initial algebra principle then supports the straightforward derivation of definitional principles and proof principles for these datatypes. This technique has been expanded to a whole methodology of structured functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Eilenberg-Moore algebras of the resumption monad are also known as F-and-M-algebras. They were used by Filinski and Støvring [10] (and later by Atkey et al [3,4]) to model data structures that interleave pure data and effects. In eager languages, the bare list monad is rarely used as a basis of backtracking computations, since the entire list structure is always computed upfront.…”
Section: Discussionmentioning
confidence: 99%
“…Eilenberg-Moore algebras of the resumption monad are also known as F-and-M-algebras. They were used by Filinski and Støvring [10] (and later by Atkey et al [3,4]) to model data structures that interleave pure data and effects. In eager languages, the bare list monad is rarely used as a basis of backtracking computations, since the entire list structure is always computed upfront.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have explored using action trees in modeling effectful constructs, including building indexed representations and interpreting them into effectful computations (Brady 2013; McBride 2011). Allowing effects in constructors of inductive types has been separately studied for simple, non-indexed types by Filinski and Stùvring (2007) and Atkey and Johann (2015). We are the first to consider indexed effectful action trees that mix data and effectful computations, while interpreting the trees into another indexed effect, allowing us to layer effectsÐin our case, layering concurrency over divergence, monotonic state, and nondeterminismÐwhile also deriving a program logic to reason about the new effect layer, based on the indexing structure.…”
Section: Related Workmentioning
confidence: 99%
“…Lifting data types into their monadic counterparts follows a general scheme. Mona found a manuscript by Atkey et al [4] that showed how to benefit from describing inductive types interleaved with effects as initial f-and-m-algebras. Their description of data types interleaved with effects was similar to the monadic lifting that Mona pursued.…”
Section: :22mentioning
confidence: 99%